Index of Orthodontic Treatment Need in Obese Adolescents - Maria Rita Giuca; Marco Pasini; Silvia Caruso; Simona Tecco; Stefano Necozione; Roberto Gatto (Hindawi Limited, 2015)
Aim. This case-control retrospective study is aimed at assessing if obese adolescents need more orthodontic treatment in comparison with normal-weight patients of the same age. Methods. The test group included 100 obese subjects (50 males and 50 females; average age: 13.09 ± 1.19 years old) and the control group included 100 normal-weight patients matched for age and sex (50 males and 50 females; average age: 13.07 ± 1.26 years old). Clinical examinations were conducted on dental casts to assess the need of orthodontic treatment, by using the Index of Orthodontic Treatment Need (IOTN) (DHC, dental health component; AC, aesthetic components). Results. No statistically significant difference (P>0.05) was observed between the two groups with regard to AC. Obese females showed a significant (P<0.05) higher percentage of DHC 3 (32%) in comparison to the normal-weight girls (22%); for the other grades of DHC and for the single kind of malocclusion, no significant difference was found. Conclusions. Obese adolescents showed a similar need for orthodontic treatment compared to normal-weight patients of the same age. However, in obese females, a slightly greater need for orthodontic treatment was observed, compared to normal-weight patients.